Ecosystem responses to the eradication of common carp Cyprinus carpio using rotenone from a reservoir in South Africa. Issue 12 (7th October 2020) - Dalu, Tatenda; Bellingan, Terence A.; Gouws, Jeanne; Impson, N. Dean; Jordaan, Martine S.; Khosa, Dumisani; Marr, Sean M.; Mofu, Lubabalo; Schumann, Mandy; Slabbert, Etienne; van der Walt, Johannes A.; Wasserman, Ryan J.; et al.
Abstract: The control of invasive alien fish populations using piscicides to alleviate impacts on native biota is a controversial conservation strategy because the collateral impacts on non‐target taxa are not well documented. This article documents the responses of water quality, plankton and macroinvertebrate communities to an eradication of the globally invasive common carp Cyprinus carpio Linnaeus 1758, using the piscicide rotenone in a small South African reservoir. Treated and untreated reservoirs were sampled before and at intervals following rotenone treatment. Sampling endpoints included water quality parameters, plankton, macroinvertebrates and fish. These endpoints were selected to gain an understanding of the ecological impacts of the treatment at various biological levels and to document possible recovery following treatment. The study showed that: (i) the common carp were successfully removed; (ii) water clarity improved following the removal of fish; (iii) invertebrate communities, including macroinvertebrates and large zooplankton, recovered within 6 months of treatment; and (iv) that small zooplankton (i.e. Rotifera) dynamics were complex but rotifer abundances had returned to pre‐treatment levels within 6 months of treatment. There was a 56% similarity between the macroinvertebrate assemblages before and 6 months after treatment, showing a substantial turnover in taxa following treatment. The phytoplankton community of the treated reservoir was dominated by blue‐green and green algae prior to the treatment. The blue‐green algal communities were not present 6 months after the treatment, possibly indicating a change in the nutrient status of the reservoir resulting from lower nutrient concentrations in the water column. The phytoplankton community of the reservoir changed from a community typical of eutrophic waters to a community typical of a lower nutrient state. Within each group, there were species changes, but we suggest these are likely to be part of the altered biological interaction dynamics resulting from fish removals, rather than a direct effect of rotenone.